2007
DOI: 10.1017/s1368980007193940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental education and income inequality on children's food intake

Abstract: Objective: To analyse the association between socio-economic indicators and diet among 2-year-old children, by assessing the independent contribution of parental education and equivalent income to food intake. Design: The analysis was based on data from a prospective birth cohort study. Information on diet was obtained using a semi-quantitative food-frequency questionnaire. Low and high intake of food was defined according to the lowest and the highest quintile of food consumption frequency, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
6
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 23 publications
5
42
6
1
Order By: Relevance
“…Our results are in accordance with a study in older school children, which showed that parental MS and/or low EL were related to a higher BMI and some selected eating habits such as a consumption of less fruit and vegetables (Lasserre et al, 2007). Association with fruit, vegetables and fatty food were also reported in toddlers of low EL families (Sausenthaler et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with a study in older school children, which showed that parental MS and/or low EL were related to a higher BMI and some selected eating habits such as a consumption of less fruit and vegetables (Lasserre et al, 2007). Association with fruit, vegetables and fatty food were also reported in toddlers of low EL families (Sausenthaler et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, some unhealthy eating habits and sedentary behaviours were more frequently observed in these children (Lasserre et al, 2007;Sausenthaler et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…In a study of the diet of 1675 preschoolers aged 1.5-4.5 years, the British National Diet and Nutrition Study reported that children from families where the head of the household performed manual work or where the mother had a lower educational attainment, met the least number of nutrient recommendations (Watt et al, 2001). Other studies conducted in Spain with children and young adults aged 2-24 years, as well as in Germany on more than 2500 two-year-old children, found similar results (Serra-Majem et al, 2002;Sausenthaler et al, 2007). Although one may argue that less educated parents have lack of information, it can also be hypothesized that these social groups value nutritional recommendations differently than more educated individuals.…”
Section: Discussionmentioning
confidence: 58%
“…Subjects: Children (n 366) aged 6-30 months and their parents. ?11, 95 % CI 20?003, 0?22) and fruits (b 5 0?10, 95 % CI 0?03, 0?16). Unfavourable socio-economic variables were associated with intakes of breads, cereals and tubers, vegetables, fruits, meats, sugars and coffee by children.…”
mentioning
confidence: 99%
“…Dietary intake can be influenced by cultural, social, demographic, economic and political factors in a society, and food habits and attitudes become consequences of these characteristics (3) . Therefore, studies have analysed the effect of social inequality on infant feeding in terms of family characteristics such as low income (4) , family food insecurity (5)(6)(7)(8) and low levels of parental education (9)(10)(11) . Family eating habits also influence children's food intake, as indicated in studies conducted primarily in developed countries (12)(13)(14) .…”
mentioning
confidence: 99%